THYMIDINE KINASE AS A CAUSATIVE FACTOR FOR TYPE 1 HERPES SIMPLEX VIRUS RESISTANCE AGAINST ACYCLOVIR - Yannie Febby Martina Lefaan; Riani Setiadhi (Dentino : Jurnal Kedokteran Gigi, 2020)
ABSTRACTBackground: Herpes Simplex Virus (HSV) infection demonstrates a high prevalence in the world. Acyclovir, one of guanine synthetic analogues, is commonly used to treat infections caused by HSV. HSV resistance against acyclovir may occur, especially in immunocompromised and immunocompetent patients, as the consequence of viral mutations. Thymidine kinase (TK) is an HSV tegument protein which plays an important role in HSV-1 resistance against acyclovir. Purpose: The purpose of this article is to review the mechanisms of TK mutation that cause HSV-1 resistance against acyclovir. Review: Acyclovir involves three stages of viral thymidine kinase phosphorylation to form acyclovir triphosphate. It prevents HSV replication by acting as a competitive inhibitor of viral DNA polymerase and a chain terminator in viral DNA synthesis. Resistance is associated with viral TK mutation that is encoded by UL23 gene. Long-term use of acyclovir may promote thymidine kinase mutation in immunocompromised and immunocompetent patients via three mechanisms, namely absolute insufficiency in TK activity (TK-negative), depletion in TK synthesis, and inability in TK phosphorylation which consequently hinders the phosphorylation of acyclovir. Herpes TK gene contains a series of cytosine and guanosine, that are important for the function and the  mutation of HSV by producing incomplete or fewer enzymes as the result of nucleotide addition or elimination in homopolymer process. Conclusion: HSV-1 resistance against acyclovir is evolved from TK mutations, in the form of TK-negative, TK low-producing, and TK altered mutants, that are unable to phosphorylate TK and accordingly disrupt acyclovir phosphorylation to convert acyclovir triphosphate. Keyword : Acyclovir, Herpes simplex virus, Resistance, Thymidine kinase